RAPD based genetic diversity, agronomic characters, and nutrition content of Timor Leste kidney bean (Phaseolus vulgaris) genotypes - MARCOS CORREIA VIDAL; Asep Setiawan; YUDIWANTI WAHYU (Society for Indonesian Biodiversity, 2019)
Abstract. Vidal MC, Setiawan A, Wahyu Y. 2019. RAPD based genetic diversity, agronomic characters, and nutrition content of Timor Leste kidney bean (Phaseolus vulgaris) genotypes. Biodiversitas 20: 2612-2619. The productivity of kidney beans (Phaseolus vulgaris L.) in Timor Leste is relatively low and needs to be improved. The increase in kidney bean yield through plant breeding, however, can only be obtained if information the genetic diversity of breeding materials is available. This study aimed to characterize agronomic characters, to assess genetic diversity and nutrient content of kidney bean in Timor Leste. The materials used in this study were 13 Timor Leste and 2 Indonesian genotypes as controls. The experimental design for the field trial was a complete randomized block design with three replications. The treatment was 13 kidney bean genotypes. The results showed that there were significant variations in agronomic characters among the genotypes tested. Result from phylogenetic trees based on the Random Amplified Polymorphic DNA (RAPD) indicated that the genetic material understudied can be grouped into three main groups. The Indonesian genotype belongs to a different group from Timor Leste genotypes. Direct selection based on seed yields produced the best eight East Timor genotypes, TL-RO3, TL-LUN, TL-LM, TL-R10, TL-LL, TL-RW, TL-LB, TL-LB, and TL-Umabano. The nutritional content of the kidney bean genotype from Timor Leste was similar to that of the Indonesian genotype. The carbohydrate content of the Timor Leste genotype was considered high (average = 59.95%), while the average fat content is low (1.71%) and the average protein content was quite moderate (18.08%).